Advanced nonlinear control strategies for a fermentation bioreactor used for ethanol production. (May 2021) - Petre, Emil; Selişteanu, Dan; Roman, Monica
Highlights: Nonlinear control structures for a bioethanol fermentation process are developed. Two adaptive control loops are built for substrate concentration and temperature. Design assumptions: unknown kinetics and inputs, noisy data, unmeasurable states. Control schemes: linearizing laws, unknown input and state observers, estimators. Goal: to increase the ethanol production and to minimize its environmental impact. Abstract: This study addresses the design of advanced control schemes implemented for a continuous fermentation process used to produce ethanol. Due to the inaccuracy of the models that express this complex process, a feasible controller is required to maximize the production of ethanol and to minimize its environmental impact, despite the existence of some significant uncertainties. Therefore, novel estimation and control schemes are designed and tested. These schemes are adaptive control laws including nonlinear estimation algorithms: a sliding mode observer to estimate the unknown influent concentration, but also state observers and parameter estimators used to estimate the unknown states and kinetics. Since the temperature is an important factor for an efficient operation of the process, an algorithm for temperature control in the bioreactor is also developed. To verify the control algorithms effectiveness, several tests performed via numerical simulations under realistic conditions are presented.